Respiratory symptoms and associated factors among women exposed to biomass fuel smoke in Sri Lanka: cross sectional study - Jayaweera, Gihani U.; Wimalasekera, Savithri W.; Goonewardena, Sampatha E. (International Journal Of Community Medicine And Public Health, 2020)
Background: Biomass fuel smoke is a leading cause of indoor air pollution. It is a known risk factor for respiratory diseases. This study was conducted to determine the prevalence of respiratory symptoms and associated factors among women exposed to biomass fuel smoke in Sri Lanka. Methods: Women (n=600) were assessed using questionnaires to determine base line data, cooking fuel use, respiratory symptoms (MRC respiratory symptoms questionnaire) and diagnosed respiratory diseases. Kitchen characteristics were determined by direct observation. Sample frequencies were calculated. Logistic regression analysis was done to determine the associations. Results: Majority (64.1%) were biomass fuel users. Their mean age was 47 years ±14 SD. Majority 99.2% were never smokers. Prevalence of cough, phlegm, cough and phlegm, wheeze, breathlessness and diagnosed asthma was 14%, 16%, 9.9%, 22%, 22.3%, and 6.3% respectively. Use of biomass fuel was related to any respiratory symptom (OR=1.9; p<0.05), cough (OR=1.9; p<0.05), phlegm (OR=2.0; p<0.05), cough and phlegm (OR=2.7; p<0.05), wheezing (OR=2.0; p<0.05) and breathlessness (OR=2.0; p<0.05). Use of biomass fuel in an outdoor kitchen was associated with cough (OR=2.8, p<0.05), phlegm (OR=4.6, p<0.05), cough and phlegm (OR=3.1, p<0.05) and breathlessness (OR=2.1, p<0.05). Use of biomass fuel in a kitchen with neither chimney nor windows was associated with phlegm (OR=2.9, p<0.05) and cough and phlegm (OR=3.0, p<0.05). Conclusions: Use of biomass fuel for cooking in an outdoor kitchen and in a kitchen with neither chimney nor windows were positively associated with respiratory symptoms in non-pregnant women exposed to biomass fuel smoke in Sri Lanka.